Detection of Plasmodium spp. in human feces - Jirků, Milan; Pomajbíková, Kateřina; Petrželková, Klára J; Hůzová, Zuzana; Modrý, David; Lukeš, Julius (Emerging infectious diseases, 2012)
Comparison of diagnostic methods for Plasmodium spp. in humans from Uganda and the Central African Republic showed that parasites can be efficiently detected by PCR in fecal samples. These results, which rely solely on PCR-based examination of feces, validate numerous estimates of the prevalence of malaria in great apes.
Keywords: Plasmodium falciparum; Protozoan Proteins; lidé; protozoální proteiny; feces; cytochromy b; Feces; Molecular Diagnostic Techniques; diagnostické techniky molekulární; Sensitivity and Specificity; tropická malárie; polymerázová řetězová reakce; Malaria, Falciparum; Cytochromes b; Polymerase Chain Reaction; senzitivita a specificita; Humans